Analysis of Passenger Satisfaction on Green Airport Blimbingsari International Service - Untung Lestari Nur Wibowo Wibowo; Quirina Ariantji Patrisia Mintje; Sabam Dany Sulung; Ikhwanul Qiram (Yayasan Ilomata, 2022)
Since 2019, Blimbingsari Airport has been designated as an International Airport with a green airport concept. This airport has received the most prestigious award in The 2022 Aga Khan Award for Architecture. Several energy efficiencies and conservation program initiatives certainly have an impact on the service facilities provided. However, this program implies an increase in the number of passengers. This increase certainly requires attention to be studied further because it is related to the airport's ability to serve the needs of service users. This study was conducted to determine the service quality of Blimbingsari International Airport based on passenger perceptions. 100 respondent were randomly selected to be the research sample. This study uses 5 (five) service quality dimensions which include 7 service variables to measure airport service quality. Data collection was carried out in mid-June 2022 by distributing a Likert scale 5 questionnaire. Data analysis used the IPA and Servqual gap methods. Based on the results of data analysis, it can be seen that there are 7 (four) service variables that are important to determine the quality of airport terminal services, namely (1) the ease of passengers in obtaining information, (2) the reliability of airport facilities and equipment, (3) the coolness and comfort of the airport terminal. , and (4) a clean airport terminal room. The servqual gap shows that 5 (five) dimensions of service quality are positive. Based on these results, it can be concluded that the service quality of Blimbingsari International Airport is very satisfying for passengers.